Analisis Tema Kemiskinan dalam Novel Al-Bidayah wa Al-Nihayah Karya Najib Mahfouz: (Kajian Sosiologi Sastra Alan Swingewood) - Hajar Aswad; Nurming Saleh; Ahmad Sirfi Fatoni (Pusat riset dan Inovasi Nasional, 2026)
This study explores the themes of poverty and educational values in the novel Al-Bidayah wa al-Nihayah by Naguib Mahfouz using the sociology of literature approach developed by Alan Swingewood. The novel is selected because it portrays the social reality of Egyptian society in the 1940s, particularly the lower class facing economic hardship, social inequality, and limited social mobility. This research employs a qualitative descriptive method through reading, note-taking, and library research. The data are drawn from narratives, dialogues, and events in the novel that reflect both poverty and educational values. The analysis is conducted by relating the textual content to its social and historical context. The findings indicate that poverty is not merely an economic issue but also a structural condition affecting the psychological, moral, and social aspects of the characters. Furthermore, the novel conveys educational values, including religious, moral, social, and cultural dimensions, which are closely linked to the realities of pre-revolutionary Egyptian society. Overall, Swingewood’s approach highlights the novel as a form of social critique as well as a medium for fostering readers’ social awareness.